Commentary to the decision of the Court of Justice of the European Union of 19 december 2019 (Oriol Junqueras case) - Bayona i Rocamora, Antoni (Journal of the Basque Parliament, 2020)
The ruling of the Court of Justice of the European Union of December 19, 2020 (Oriol Junqueras case) is of special relevance because it determines when and how the status of member of the European Parliament and also the European parliamentary immunity are acquired. Until the ruling, there was no clear position on the matter, and the European court resolves it by prioritizing the exercise of the right to vote over other conditions eventually established by the law of the Member States. The judgment of the Court of Justice of the European Union answers the preliminary question submitted by the Supreme Court in the criminal case of the procés and establishes an interpretative doctrine of European law in the sense that the status of deputy and the immunity associated with the position occur from the moment of the official announcement of the electoral results. However, the judgment has not been able to be effectively applied due to the Supreme Court’s decision not to suspend the main cause and to pass judgment before hearing the opinion of the European court, which highlights a misuse of the preliminary ruling procedure.